2023
DOI: 10.3390/jcm12031122
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimum Mandibular Reconstruction for Dental Occlusal Rehabilitation: From Preoperative Virtual Surgery to Autogenous Particulate Cancellous Bone and Marrow Graft with Custom-Made Titanium Mesh—A Retrospective Study

Abstract: The purpose of this retrospective study was to evaluate computer-assisted virtual surgery and the outcomes of mandibular reconstruction using an autogenous particulate cancellous bone and marrow (PCBM) graft combined with a custom-made titanium mesh (TiMesh) using a three-dimensional (3D) printing model. Eighteen consecutive patients were included, and preoperative virtual simulation surgery was performed using digital data. Segmental bone defects showed deviation of the mandible due to displacement of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A similar situation seems to also occur in humans following the fracture or loss of complete segments of the mandible, in which the direction of stump displacement depends on the localization of the defect in relation to the masticatory muscles. This can lead to either a convergence of the stumps and, thus, to defect reduction, or a divergence of the stumps and, consequently, to the enlargement of the defect region (Onodera et al, 2023). In our study, the observed gap minimization may have likewise resulted from the sudden mobility of the stumps due to severance of muscles or, alternatively, from a more active process directing these mechanical tissue readjustments.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation seems to also occur in humans following the fracture or loss of complete segments of the mandible, in which the direction of stump displacement depends on the localization of the defect in relation to the masticatory muscles. This can lead to either a convergence of the stumps and, thus, to defect reduction, or a divergence of the stumps and, consequently, to the enlargement of the defect region (Onodera et al, 2023). In our study, the observed gap minimization may have likewise resulted from the sudden mobility of the stumps due to severance of muscles or, alternatively, from a more active process directing these mechanical tissue readjustments.…”
Section: Discussionmentioning
confidence: 99%
“…3D-printed surgical adjuncts can provide a precise fit with the bone and can transfer surgical plans to the actual operations. Additionally, autologous iliac cancellous bone is a favored choice for maxillofacial reconstruction due to its plasticity and sufficient volume, while maintaining the iliac crest's contour [15]. It presents good plasticity and can provide a sufficient quantity of bone while preserving the external contour of the iliac crest.…”
Section: Introductionmentioning
confidence: 99%